Find the positive integer n , for which ⌊ lo g 2 1 ⌋ + ⌊ lo g 2 2 ⌋ + ⌊ lo g 2 3 ⌋ + ⋯ + ⌊ lo g 2 n ⌋ = 1 9 9 4 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Another way of finding the sum would be to consider the series 1 + x + x 2 + x 3 . . . x n = x − 1 x n + 1 − 1 , differentiating it term-wise and then multiplying it by x . After that, just substitute x = 2 and Io, you have the same series get equaled to ( n − 1 ) ( 2 n + 1 ) + 2 .
Log in to reply
Thanks. I knew there should be a simpler way.
That's how i did it too.
Well said.
Can also get to the expression
( n − 1 ) ( 2 n + 1 ) + 2
by noticing that we have a sum, in binary, of the form
1 . . . 1 0 + 1 . . . 1 0 0 + 1 . . . 1 0 0 0 + . . . + 1 0 . . . 0
where each addend has the same number of digits, and that is equal to
( 2 n + 1 − 2 2 ) + ( 2 n + 1 − 2 3 ) + . . . + ( 2 n + 1 − 2 n ) + 2 n + 1 = ( n − 1 ) ( 2 n + 1 ) + 2
This can also be generalized using the result from my solution on this problem.
Converting it into a double sum and evaluating it gives us a form and then a bit of analysis gives us the value of n . First, we take the sum in LHS as S . Now, we bound n between two consecutive powers of 2 . Let the power of 2 which acts as the lower bound be 2 m for some non-negative m . Then, we have,
2 m ≤ n < 2 m + 1 ⟹ S = ⎝ ⎜ ⎛ k = 0 ∑ m − 1 j = 2 k ∑ 2 k + 1 − 1 k ⎠ ⎟ ⎞ + k = 2 m ∑ n m
From that solution I linked, we get that this evaluates to,
S = ( m − 2 ) 2 m + 2 + k = 2 m ∑ n m
Now, comes the analysis part. Calculate S for n = 2 7 , 2 8 and 2 9 with m = 7 , 8 , 9 respectively (this agrees with the bounds). It becomes obvious that we need m = 8 for the S to equal 1 9 9 4 for some non-negative n that satisfies our boundings. Then,
S = 1 9 9 4 ⟹ m = 8 ⟹ 1 5 3 8 + k = 2 5 6 ∑ n 8 = 1 9 9 4 ⟹ ( n − 2 5 6 + 1 ) 8 = 4 5 6 ⟹ n − 2 5 5 = 5 7 ⟹ n = 3 1 2
Problem Loading...
Note Loading...
Set Loading...
Let k = 2 i + j , where i , j and k are non-negative integer and j < 2 i then the k t h term of the expression is:
a k = ⌊ lo g 2 k ⌋ = ⌊ lo g 2 ( 2 i + j ) ⌋ = i
That is: For n = 1 For 2 ≤ n ≤ 3 For 4 ≤ n ≤ 7 For 8 ≤ n ≤ 1 5 ⇒ a k = 0 ⇒ a k = 1 ⇒ a k = 2 ⇒ a k = 3 . . .
Therefore,
S = ⌊ lo g 2 1 ⌋ + ⌊ lo g 2 2 ⌋ + ⌊ lo g 2 3 ⌋ + . . . + ⌊ lo g 2 n ⌋ = i = 1 ∑ m i ( 2 i ) = 1 ( 2 ) + 2 ( 4 ) + 3 ( 8 ) + 4 ( 1 6 ) + 5 ( 3 2 ) + 6 ( 6 4 ) + 7 ( 1 2 8 ) + . . . = 2 + 8 + 2 4 + 6 4 + 1 6 0 + 3 8 4 + 8 9 6 + . . . = 1 5 3 8 + 8 ( j + 1 ) = 1 9 9 4
⇒ j = 8 1 9 9 4 − 1 5 3 8 − 1 = 5 6
Now, we know that the first a k = 8 is when i = 8 and k = 2 8 = 2 5 6
Therefore, n = k + j = 2 i + j = 2 8 + 5 6 = 2 5 6 + 5 6 = 3 1 2